Implementing the KiVA Program to Prevent Bullying: A Qualitative Phenomenological Study in Indonesian Elementary Schools - M.Noer, Rachmawaty; Agusthia, Mira; Dasaryandi, Kiki Rizki; Wulandari, Yulianti (Journal of Applied Nursing and Health, 2025)
Background: Bullying in Indonesian schools remains a major issue affecting children’s psychological, social, and academic well-being. Reports from KPAI and UNICEF indicate that prevention at the elementary level remains inadequate. While most studies focus on punishment and counseling, research on community-based programs such as the KiVA Method—promoting awareness, empathy, and conflict management—is limited, underscoring the need to explore their application in Indonesia’s socio-cultural context. Methods: This study employed a qualitative case study approach to explore the experiences of teachers, counselors, students, and parents in implementing the KiVA Method. Participants were selected purposively, including those actively involved in or experienced with the program for at least one semester. Individuals who were not actively participating or had communication barriers were excluded. Of 30 invited participants, 25 met the criteria and agreed to join, while 5 declined due to time, unwillingness, or health issues. Data were gathered through 45–60-minute interviews and field observations, with official approval from the Education Office and the school. Thematic analysis using NVivo 12 followed COREQ guidelines to ensure research transparency and credibility. Results: Of the 25 participants, consisting of 8 teachers, 4 counselors, 10 students, and 3 parents, it was found that implementing the KiVA Method increased school community awareness of bullying behavior, strengthened social empathy, and encouraged positive student interactions. Teachers and counselors reported a significant decrease in bullying incidents, while students felt safer and more supported in an inclusive learning environment. Thematic analysis revealed four main themes: increased social-emotional literacy, changes in classroom communication patterns, strengthening teachers' roles as empathetic facilitators, and parental support for implementing anti-bullying values. Conclusion: The research results indicate that the KiVA Method positively contributes to building collective awareness of bullying, strengthening empathy among school members, and creating a supportive and inclusive learning climate. However, the program's long-term effectiveness requires further research with a longitudinal design and a cross-school comparative approach to assess its sustainability in Indonesia's primary education context.